2020
DOI: 10.1038/s41467-020-16740-5
|View full text |Cite
|
Sign up to set email alerts
|

Tunable resistivity exponents in the metallic phase of epitaxial nickelates

Abstract: We report a detailed analysis of the electrical resistivity exponent of thin films of NdNiO 3 as a function of epitaxial strain. Thin films under low strain conditions show a linear dependence of the resistivity versus temperature, consistent with a classical Fermi gas ruled by electronphonon interactions. In addition, the apparent temperature exponent, n, can be tuned with the epitaxial strain between n = 1 and n = 3. We discuss the critical role played by quenched random disorder in the value of n. Our work … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 69 publications
(88 reference statements)
2
38
1
Order By: Relevance
“…To gain further insights into the thickness-dependent MIT, we fit the metallic resistivity of the SLs with n ≥ 3 using the power law ρ = ρ 0 + AT α , where the parameter A is determined by the strength of the electron scattering. 44 The power-law exponent α is found to increase from α = 1.0 ± 0.1 for n ≥ 5 to α = 1.90 ± 0.01 for n = 4 and end up with α = 3.14 ± 0.01 for n = 3 ( Figure S5 ). The departure from a linear scaling in perovskite nickelates has been ascribed to a joint effect of epitaxial strain and oxygen vacancies.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…To gain further insights into the thickness-dependent MIT, we fit the metallic resistivity of the SLs with n ≥ 3 using the power law ρ = ρ 0 + AT α , where the parameter A is determined by the strength of the electron scattering. 44 The power-law exponent α is found to increase from α = 1.0 ± 0.1 for n ≥ 5 to α = 1.90 ± 0.01 for n = 4 and end up with α = 3.14 ± 0.01 for n = 3 ( Figure S5 ). The departure from a linear scaling in perovskite nickelates has been ascribed to a joint effect of epitaxial strain and oxygen vacancies.…”
mentioning
confidence: 94%
“…The departure from a linear scaling in perovskite nickelates has been ascribed to a joint effect of epitaxial strain and oxygen vacancies. 44 Considering the fact that all SLs are coherently strained to the NGO substrate, the larger α for n = 3, 4 is probably due to the increasing amounts of oxygen vacancies with ultrathin NNO layers. This can also contribute to the enhanced resistivity and T MIT by creating local disproportionation of NiO 6 octahedra.…”
mentioning
confidence: 99%
“…2d, a cuprate-like linear-T -resistivity is observed in NNO in a ultra-wide temperature range (about 400 K). In our previous works, we showed that this T -linear behaviour of resistivity can be achieved in optimized NNO films with low epitaxial strain and low oxygen vacancy content [34] and, more interestingly, it has signatures of Planckian dissipation [35]. With the further increase of T, the rise of ρ(T) shows an obvious deviation from the linear dependence, which is caused by the addition of a parallel saturation resistance that takes over the behaviour in the high temperature regime [4,13,29].…”
mentioning
confidence: 74%
“…In fact, this compound is attracting significant attention, since superconductivity was reported in the infinite layer system Nd 1−x Sr x NiO 2 [31], and is a remarkable example of a material whose metallic behavior has been particularly difficult to classify [25,32,33]. For the present study we have used high quality epitaxial NNO films grown on LaAlO 3 substrates, which have been characterized in detail in our previous work [34,35]. High-angle annular dark field (HAADF) STEM image shown in Supplementary Section 1 demonstrates the high crystalline quality of the NNO films with an atomically sharp interface with the substrate.…”
mentioning
confidence: 99%
“…These perovskite nickelates have been grown by various techniques. The most popular is pulsed laser deposition (PLD) [18][19][20][21], but sputtering [22,23] and molecular beam epitaxy [24] have also been used. At this stage, the main difficulty lies in the stabilization of the unfavorable high 3+ valence of Ni (instead of its most preferred 2+), reproducibility and off-stoichiometry issues have been reported in the literature [25].…”
Section: Epitaxial-growth Aspectsmentioning
confidence: 99%